A novel terbium doping effect on physical properties of lead sulfide nanostructures: A facile synthesis and characterization. Issue 20 (28th October 2020) - Shkir, Mohd.; Chandekar, Kamlesh V.; Alshahrani, Thamraa; Kumar, Ashwani; AlFaify, Salem
Abstract: Abstract : Lead sulfide (PbS) is having tremendous applications in the field of optoelectronics. Hence, a facile low temperature synthesis of PbS with different contents of terbium (Tb) has been achieved and investigated for structure–optic–dielectric–electrical properties. The structure confirmation was observed through the X-ray diffraction and Rietveld refinement process which approved a monophasic cubic structure. Rietveld refinement gives a best-fitting profile of the prepared products. The crystallite size was estimated to be in range of 15–21 nm. FT-Raman study also approved the single-phase PbS with all characteristic modes. For further confirmation of composition, homogeneity, and Tb in the final product, the EDX/SEM e-mapping was carried out. The morphological investigation was carried out through SEM which revealed that the shape and size are greatly influenced by Tb content addition in PbS. The energy gap ( E g ) was estimated in the range of 1.42–1.62 eV for all Tb@PbS, and the largest E g value was observed for 0.5 wt% Tb@PbS. The dielectric constant values are calculated in the range of 16–25 in the tested frequency region. The ac electrical conductivity was enhanced with frequency, and a charge transport mechanism is related to a correlated barrier hoping model in the prepared samples.